A study on the efficiency and effectiveness of the Malaysian anti-corruption commission with special reference to the international commission against corruption, Hong Kong / Muhammad Farhan Abd Ghani, Muhammad Aizat Mohd Zaid and Muhammad Hazwan Mohd Hussin - Abd Ghani, Muhammad Farhan; Mohd Zaid, Muhammad Aizat; Mohd Hussin, Muhammad Hazwan (2011)
This research analyzed on the different features of the Malaysian Anti-Corruption Commission (MACC) with the Independent Commission Against Corruption (ICAC), Hong Kong. The differences were scrutinized to identify whether such differences of the features contribute to the efficiency and effectiveness of the MACC. Based on the differences identified, some recommendations were made with the intention to improve the efficiency and effectiveness of the MACC. The first chapter goes into the essences and structures of the research. In the second chapter, it focused on the different features of MACC and ICAC, Hong Kong which leads to their efficiency and effectiveness. The third chapter discussed on the special features of anti-corruption agency from other countries like Singapore, New South Wales and Finland. In the fourth chapter, the researchers outlined the findings of the research based on an interview and several emails from respondents. The research was concluded in the last chapter and some recommendations were made to propose on some improvements that can be imposed to the MACC to ensure its efficiency and its effectiveness in handling corruption in Malaysia.